ANALISIS PENGARUH KOMUNIKASI EFEKTIF DAN KOORDINASI TERHADAP MOTIVASI KERJA DAMPAKNYA TERHADAP KINERJA KARYAWAN PT GARUDA INDONESIA (Persero) Tbk - Ariyanti, Anik (JURNAL ILMIAH M-PROGRESS, 2019)
This study aims to determine the effect of effective communication and coordination through work motivation on the performance of employees of PT Garuda Indonesia (Persero) Tbk. The sample in this study amounted to 100 people or 25% of the total population of 400 people. This research uses quantitative descriptive analysis method. Methods of data analysis using the Classical Assumption Test, Regression Test, Determination Coefficient, Hypothesis Test and Path Analysis. The test results show that effective communication and direct coordination have a positive and significant effect on work motivation. Effective communication and direct coordination have a positive and significant effect on performance. Indirectly effective communication and coordination through work motivation have no significant effect on performance. The total effect of effective communication on performance through work motivation is equal to 0.327 and the effect of coordination on performance through work motivation is 0.588. The total value of R2 is 0.593 or 59.3%, meaning that communication is effective, coordination and motivation are able to explain the performance of 59%, the remaining 40.7% is explained by other variables.Â Keywords: effective communication, coordination, work motivation and performance